Do social factors contribute to Sovereign (Country) default risk premium? - Ahmed, Zeshan; Ali, Rosalan; Johari, Jalila (Elite Scientific Forum, 2024)
More and more research has indicated the importance of incorporating ESG factors into key financial management decisions. Social factors in particular are understood to be an indication of overall strength of national wellbeing and hence credit resilience. Therefore, with this paper, we examined initially the role of specific macroeconomic factors into pricing the sovereign credit default swaps (S-CDS). We then included into our model certain factors that collectively indicate a country’s overall social performance. Subsequently, we explored for any variation in findings by segregating countries across various income levels and regional classifications. With this paper, we intend to guide national governments on how they can benefit from lower borrowing costs by simply improving their social indicators. Our findings confirm that some, not all, social factors do play a role in sending signals to financial markets to price the credit default spreads for sovereign borrowers. Hence, national governments and policy makers can prioritize improving their social indicators given their respective individualities.